The role of investor protection in corporate governance and accounting harmonization: Cross-country analysis in Asia - Ratna Wardhani (Journal of Economics, Business, and Accountancy Ventura, 2015)
The purpose of this research is to analyze the effect of law system for investor protection on implementation of corporate governance at company level and degree of convergence of local accounting standards to IFRS (International Financial Reporting Standards). The result shows that investor protection has positive effect on implementation of corporate governance and degree of convergence of local standard to IFRS. The evidence is consistent with the argument that firm can establish law environment well for their own, but the quality of corporate investor protection via implementation of corporate governance mechanisms will depend on efficiency of judicial system of the country where the firm operates; and the quality of accounting standard in one country is a signal of country’s commitment to investor protection in order to provide good protection for its investor; a country will tend to adopt higher quality of accounting standard to ensure financial reporting transparency. This indicates that investor protection can be the key to the quality of other governance mechanisms, both at institutional level such as accounting standards, and also at firm level such as corporate governance implementation.